Implementasi Metode BIN BAZ dalam Pembelajaran Tahsin Santri Kelas X MA Islamic Centre Bin Baz - Muadz Fathi; Enung Hasanah (At Turots: Jurnal Pendidikan Islam, 2023)
The Bin Baz Method (MBB) is one of the Quran learning methods developed by the Tahfidz Team of the Islamic Center Bin Baz Yogyakarta Boarding School. This study describes the implementation of the MBB method, its teaching techniques, and identifies supporting and inhibiting factors in the tenth-grade Madrasah Aliyah class. The research adopts a descriptive qualitative approach with a flow model analysis technique. The results indicate that the Quran learning process using the MBB method involves eight stages. Supporting factors include independent students, a conducive environment, rewards for students, and exemplary teachers. Learning obstacles include limited activity space, differing teacher standards, and the busy boarding school schedule that sometimes causes students to feel tired and less enthusiastic about learning.